Prolonged Survival following Repetitive Stereotactic Radiosurgery in a Patient with Intracranial Metastatic Renal Cell Carcinoma - Ethan A. Ferrel; Andrew T. Roehrig; Wayne T. Lamoreaux; Alexander R. Mackay; Robert K. Fairbanks; Jason A. Call; Jonathan D. Carlson; Benjamin C. Ling; John J. Demakas; Barton S. Cooke; Aaron Wagner; Christopher M. Lee (Case Reports in Neurological Medicine)
Patients with metastatic renal cell carcinoma (RCC) to the brain have a very poor prognosis of three months if left untreated. SRS is an effective treatment modality in numerous patients. This case exemplifies the utility of stereotactic radiosurgery (SRS) in prolonging survival and maintaining quality of life in a patient with RCC. This 64-year-old female patient initially presented to her primary care physician 22 months after a left nephrectomy for RCC with complaints of mild, intermittent headaches and difficulty with balance. An MRI revealed five cerebellar lesions suspicious for intracranial metastasis. The patient’s first GKRS treatment targeted four lesions with 22 Gy at the 50% isodose line. She underwent a total of seven GKRS treatments over the next 60 months for recurrent metastases to the brain. 72 months and 12 months have now passed since her brain metastases were first discovered and since her last GKRS treatment, respectively, and this woman is alive with considerable quality of life and no evidence of metastatic reoccurrence. This case shows that repeated GKRS treatments, with minimal surgical intervention, can effectively treat multiple intracranial lesions in select patients, prolonging survival and avoiding iatrogenic neurocognitive decline while maintaining a high quality of life.